Stability Analysis of Impulsive Control Systems with Finite and Infinite Delays - Xuling Wang; Xiaodi Li; Gani Tr. Stamov (The Scientific World Journal)
This paper studies impulsive control systems with finite and infinite delays. Several stability criteria are established by employing the largest and smallest eigenvalue of matrix. Our sufficient conditions are less restrictive than the ones in the earlier literature. Moreover, it is shown that by using impulsive control, the delay systems can be stabilized even if it contains no stable matrix. Finally, some numerical examples are discussed to illustrate the theoretical results.